The use of virtual reality (VR) exposure for reducing contamination fear and disgust: Can VR be an effective alternative exposure technique to in vivo? - Inozu, Mujgan; Celikcan, Ufuk; Akin, Burcin; Mustafaoğlu Çiçek, Nuray (Elsevier, 2020)
Background and objectives: Virtual reality (VR) has become a new tool in psychological research and application. Although several studies have investigated its triggering and reducing role in anxiety via VR-based exposure and response prevention (VR-ERP) across different psychopathologies, its efficiency in contamination fear and reduction of disgust are yet to be examined. The study contributes to the field by investigating the effectiveness of the VR-ERP on the reduction of anxiety, disgust and urge to wash levels using an experimental design. Methods: A total of 21 non-clinical participants with high contamination fear were randomly assigned to experimental (n = 9) and control (n = 12) groups. The experimental group was exposed to repeated VR-ERP sessions. Results: After a minimum of three VR-ERP sessions, the experimental group scored significantly lower than the control group on the anxiety, disgust, and urge to wash hands scores. Limitations: A small sample size, an analogue sample, and a generic virtual scenario content were potential limitations of the study. Conclusions: The results indicated that the VR-ERP can be an efficient and alternative exposure tool in the reduction of anxiety, disgust, and urge to wash hands. The theoretical and clinical applications of the VR-ERP in the treatment of contamination-based OCD symptoms were discussed in light of our findings.
Keywords: Virtual reality; Exposure therapies; Contamination anxiety; OCD; Disgust